PENGARUH KEPEMIMPINAN KINERJA DAN KEPUASAN KERJA PT. MEGAH SEMBADA INDUSTRIES: PENGARUH KEPEMIMPINAN KINERJA DAN KEPUASAN KERJA PT. MEGAH SEMBADA INDUSTRIES - Sumardi; Duta Maulana (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the effect of leadership on employee performance and the influence of leadership on job statisfaction and to determine the effect of employee performance on job statisfaction. The research is associative and the data collection technique uses primary data in the form of questionnaires distributed to all employees who work in the company with population of 42 and the sampling technique uses saturated sampling. The result showed that leadership has a positive and significant influence on employee performance and leadership has a positive and significant influence on job statisfaction and employee performance has a positive and significant influence on job statisfaction.